2021
DOI: 10.1111/jade.12348
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Barriers: Educating Design Students about Inclusive Design through an Authentic Learning Framework

Abstract: Current studies in design education suggest that students and educators base their designs on what they already know about themselves and their peers, or on stereotypical notions of others. This article presents a critical examination of a pedagogical approach employed in several architecture and interior design studios to determine how best to develop student understanding of how to design for real users and users with abilities different from themselves. This authentic learning approach with spatial design s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This real-world connection enables 'authentic learning' to take place (Herrington et al, 2014). Assisting students to develop complex skills such as systems-thinking is strengthened by this approach, as Rieger (2021) suggests in relation to the teaching of inclusive design. Irwin et al (2020) discuss how complicated problems can be answered by solutions of varying complexity and expertise in the Winterhouse Social Design Pathways Matrix (Figure 8).…”
Section: Discussion On Teaching and Learningmentioning
confidence: 99%
“…This real-world connection enables 'authentic learning' to take place (Herrington et al, 2014). Assisting students to develop complex skills such as systems-thinking is strengthened by this approach, as Rieger (2021) suggests in relation to the teaching of inclusive design. Irwin et al (2020) discuss how complicated problems can be answered by solutions of varying complexity and expertise in the Winterhouse Social Design Pathways Matrix (Figure 8).…”
Section: Discussion On Teaching and Learningmentioning
confidence: 99%
“…As far as the environmental art design specialty is concerned, the environmental art design specialty is characterized by crossfertilization, which involves a wide range of disciplines and a deeper degree of professional subdivision. Innovating the teaching and training system and training standards of the environmental art design profession can realize the cross-fertilization of the discipline of environmental art design profession with the scientific and technological revolution and industrial change, and the cross-fertilization of the professional curriculum with multidisciplinary knowledge [4][5][6][7]. Oriented by the all-media perspective, which aligns with the ability cultivation requirements of the environmental art design profession, it can give full play to the teaching advantages of project-based teaching and make teaching the environmental art design professional courses more targeted [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…According to recent research that addressed authentic learning in undergraduate design projects, students benefitted in many ways, from developing an understanding of the abilities of users unlike themselves, to creating connections to potential clients (Rieger and Rolfe, 2021;Wilson & Schwier, 2009). In sum, I found that there were both advantages and disadvantages that I needed to heed while implementing the body biography sessions.…”
Section: Interdisciplinaritymentioning
confidence: 99%